(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
Rabindranath Tagore’s novel Ghare-Baire was published in sobujpotro from Baishakh to Phalgun in Bangabda 1322. In Bangabda 1323 Ghare-Baire was first published. Rabindranath Tagore wrote his Novel Garhe-Baire against the background of the Swadeshi movement of Bengal. In this novel the real position of women of that era is revealed in the context of the story of Bimala. Bimala is a bride of a Zamindar family, her husband is a highly educated liberal man. Nikhilesh, husband of Bimala, is a character who is ahead of his time, totally different from the stereotype patriarchal social system of that era. He wants to get Bimala not only in the small confines of the house but also in the larger world - outside the house. In the novel Ghare-Baire we will also see the two wives, Nikhilesh’s brother’s wives, who are forced to accept widowhood due to their husband’s promiscuity and perversity. This is their fate as brides of the Zamindar family. The two wives of the husband’s brother of Bimala are living their lives of endless pain in two different paths. Towards the end of 19th Century women started to nurture their desire for emancipation, and the right of education. This indomitable desire started to flourish in the beginning of the 20th century. The bonds of social customs accumulated in their blood for ages were pulling them back. The booming part of the 19th Century is the very beginning of the 20th century. That’s why just as Bimala feels attracted to Nikhilesh’s advice to go out and runs madly at Sandeep’s charms, from that point also her inner conscience of chastity starts to haunt her terribly in self-torture. Rabindranath Tagore wrote this novel to enlightening the position of women in early twentieth century, when the maximum numbers of women are not allowed to go for education. Specially the married women are confined in their in-law’s house. In this age Nikhilesh, Bimala and Sandeep are created in a different way.